Analisa Dampak Implementasi Modul Manajemen Proyek Odoo ERP Pada Perusahaan Jasa Konstruksi PT. X - Lucia Stefanie T Suwandy; Yulia Yulia; Eveline Cynthia Irawan (Jurnal Infra, 2022)
Information technology has an important role in the business world. However, there are still companies that have not utilized information technology. PT. X is a construction company that still does all the work manually. This resulted in the emergence of problems in the company, among others: in obtaining information it takes longer time because the data contained in the company has not been integrated. Then, the possibility of problems from negligence committed by employees, such as there is data that is forgotten to be entered into the recording of company data. The Enterprise Resource Planning program was created to try to overcome the problems that occurred at PT. X. For that the platform chosen is Odoo because it has many advantages such as easy to configure and customize the module. To overcome the problems that exist in the company, a Critical Path Method (CPM) function is made to support the company's business processes in project management. To measure the success of the Odoo ERP program implementation, user satisfaction analysis was carried out using the Doll and Torkzadeh (1998) method. From the analysis of the implementation of the Odoo ERP program in the company, it can be concluded that the Odoo ERP program has a good impact on meeting company needs properly and quickly.